Comparison of Classification Models for Predicting Admission Outcomes of Prospective Students with Disabilities - Rosihon Anwar; Mohamad Irfan; Ilham Nurjaman (CV. Generasi Intelektual Digital, 2026)
Students with disabilities are a group that requires special attention in the admission process at universities, especially at State Islamic Higher Education Institutions (PTKIN). Although inclusive policies have been implemented, challenges in implementation in the field are still quite significant, especially in terms of equal access and the readiness of educational institutions. This study aims to analyze the opportunities and challenges of accepting students with disabilities at PTKIN through a machine learning approach to predict the factors that influence selection graduation. The research data consists of 80 prospective students with disabilities who participated in the PTKIN selection, covering variables such as gender, province of origin, previous education, school accreditation, and type of disability. The research process included data cleaning, feature engineering (including categorical encoding and recategorization of disability variables), and data balancing using the SMOTE method. Next, model training was carried out using three main algorithms, namely Support Vector Machine (SVM), Random Forest, and XGBoost, as well as model combination (ensemble voting classifier) for performance comparison. The results show that the SVM (RBF kernel) model provides the best performance with an accuracy of 80% and an F1-score of 0.88 for the “Pass” class. This model outperforms Random Forest and XGBoost, which have an accuracy of 65% each. The most influential factors for graduation are the province of origin, disability category, and previous form of education. These findings indicate that the acceptance of students with disabilities at PTKIN is still influenced by geographical factors and educational background, so affirmative policies need to be directed at expanding access for people with disabilities from certain regions and backgrounds. The machine learning approach has proven to be effective as a tool for analyzing inclusive education policies in the PTKIN environment.